A GREEN AND EFFICIENT HPLC-DAD METHOD FOR THE ANALYSIS OF PHENOLIC COMPOUNDS IN ORANGE WASTE - Mirella T. Ferreira Ranzeti; Gabriela Cremasco; Daniel Rinaldo (Química Nova)
This study presents a sustainable high-performance liquid chromatography photodiode array detection (HPLC-DAD) method for analyzing polar phenolic compounds in sweet orange (Citrus sinensis) residues. Fractional factorial design was used to identify significant variables affecting method efficiency, which were subsequently optimized using Doehlert design. The optimized conditions were: initial ethanol percentage = 20%, final ethanol percentage = 75.3%, analysis temperature = 40 °C, percentage of acetic acid in water = 0.4%, flow rate = 0.5 mL min-1, time = 35 min, and C-18 column (250 × 4.6 mm). The method effectively separated and allowed the identification of phenolic acids, vitexin, and hesperidin, while adhering to green chemistry principles, making it a safer and more environmentally friendly alternative to traditional methods, complying with principles 2, 4, 5, 6, 7, 8, 9, 10, 11 and 12 of the Green Analytical Chemistry (GAC), bringing a low cost of analysis, with little energy expenditure, low toxic solvents from renewable sources, little waste generation and safety in operation.